The Effect of Abusive Supervision on Employees’ Work Procrastination Behavior - He, Qi; Wu, Mengyun; Wu, Wenhao; Fu, Jingtao (Frontiers in Psychology, 2021)
Work procrastination is a retreat behavior associated with negative cognitive experience and it results in great losses to individual as well as organizational development. Understanding the antecedents of employees’ work procrastination behavior contributes to lower frequency of its occurrence. This research builds a dual-moderated mediation model from the perspective of cognitive appraisal theory and explored work procrastination behavior of employees subjected to abusive supervision. With 378 valid returned questionnaires, data collected from 32 companies in Beijing, Shanghai, Tianjin, and Chongqing supports our hypotheses. This result has enriched the understanding of work procrastination behavior and provided practical implications to avoide its negative effects.